Potential of urban and peri-urban agriculture in the Global South: Priority investments for innovation - Prain, Gordon (Commission on Sustainable Agriculture Intensification, 2022)
Cities are highly visible centers of mass consumption of food and vast excretion of waste; they are less often associated with the production of food. Yet closer observation of cities in the Global South reveals that they are also locations of food production. This report describes the major challenges affecting crop cultivation and animal raising as well as food consumption in and around cities, where many households are poorly fed, negatively affected by unsustainable urbanization processes, and threatened with a warming and disease-prone world. It asks whether urban agriculture can mitigate these challenges, how it is affected by them, and if, indeed, it may exacerbate them. These questions demand a detailed consideration of the definitions of urban agriculture, especially between agricultural activities within the built-up environment and peri-urban agriculture conducted on the edge of the city and in the surrounding areas. Both of these are included in our analysis of urban and peri-urban agriculture (UPA).